Efektivitas Strategi Non – Celebrity Endorsement Dan Membentuk Brand Image Dalam Mempengaruhi Keputusan Pembelian Konsumen Pada UMKM Tiebymin - Nurjannah, Ratih; Sudrajat, Ajat (Politeknik Negeri Ambon, 2024)
In this highly competitive age, consumers are often impacted by widespread advertising. There are many factors that can influence the successful implementation of a non-celebrity endorsement strategy. One of the factors is how the right endorser is selected by MSMEs and how the message conveyed can be understood by consumers. This forms a good brand image in the minds of consumers, which in turn influences the purchase decision of the product. The study with quantitative research involved the participation of 100 respondents and applied the SEM analysis method using the SmartPLS 4.0 tool. Tests include measurement model test, structural model test, and hypothesis testing. The results of this study show that in the validity and reliability tests, the variables of non-celebrity endorsement (X1), brand image (X2), and purchase decision (Y) are considered valid and reliable because all values meet the predetermined standards. The R-Square of non-celebrity endorsement (X1), brand image (X2), and purchase decision (Y) shows that the effect is moderate, which is 51.5%. Therefore, the results of this study say that the non-celebrity support strategy and forming a brand image can influence the purchasing decisions of Tiebymin MSME consumers